Labour productivity as a factor of sustainable economic development - BALU, Mariana-Elena; MLADEN, Luise (Annals of Spiru Haret University. Economic Series, 2010)
Romania aims at reducing the economic and social gaps to the EU developed Member States. This requires an economic sustainable growth. An increased labour productivity is one of the main factors of competitiveness at national level and of sustainable economic development.